Determinación de la correlación entre la demanda atmosférica y contenido de humedad del suelo para establecer la lámina de riego a aplicar en el sistema agroforestal con café (Coffea arábica L.) en la Quinta Experimental “La Argelia” - Andino Armijos, Stefany Lisbeth (2024)
The present research was carried out in order to obtain the appropriate irrigation depth for the agroforestry system of coffee (Coffea arábica L.) with drip irrigation in the Los Molinos sector belonging to the La Argelia Experimental Farm of the National University of Loja, between the months of November and December 2023. To establish this irrigation depth for coffee cultivation, it began with the determination of the soil hydro-physical constants (Saturation, FC, and PWP), infiltration rate, as well as the installation and calibration of tensiometers to obtain the adjustment equations of soil moisture content with measured matric potential. The moisture levels evaluated were: Block 1 (-25 kPa); Block 2 (-35 kPa); and Block 3 (-45 kPa), continuously replenishing the necessary water volume based on the readings of the tensiometers placed in each block until reaching FC (10 kPa). Thus, the water consumption for blocks B1, B2, and B3 were 158 mm, 137 mm, and 68 mm respectively, provided in 6, 4, and 1 irrigations over the two months of evaluation. Meanwhile, the water requirement with the evaporimeter type A was 142,9 and 125,7 for the months of November and December respectively, showing a low correlation between these two parameters. Therefore, upon obtaining inconclusive results and evidencing that there was a greater water consumption in T1, due to the higher activity of the roots as the plants suffer less water stress with a smaller irrigation interval compared to the other treatments, it is determined that the irrigation depth of T1 (-10kPa to -25kPa) should be applied for coffee cultivation.